Pencegahan Komplikasi Hipertensi Pada Lanjut Usia Dengan Edukasi dan Teknik Relaksasi Otot Progresif - Kristamuliana Kristamuliana; Andi Buanasari (Unika Santu Paulus Ruteng, 2024)
Every older adult has a risk of suffering from chronic disease including hypertension. Older adults who live in Nursing Homes in Manado also have the same risk. The result of the study showed that there are 50% of older adults in Senja Cerah Nursing Home and 30% of older adults in Damai Ranomuut nursing home suffering hypertension. Appropriate action is needed to solve this problem so that, the complications of hypertension can be prevented. The solution to this problem is education about hypertension and progressive muscle relaxation techniques exercise. This activity is divided into three stages: preparation, implementation, and evaluation. Preparations made include coordinating with the orphanage, preparing the place for activities, and preparing materials. The implementation of the activity is divided into two parts: education about hypertension and progressive muscle relaxation techniques exercise. The evaluation carried out are structural evaluation and process evaluation. Participants who participated in this activity totaled 24 older adults. The evaluations result showed that there is an increase in the knowledge of the older adults about hypertension after education and older adults are able to perform movements in progressive muscle relaxation technique exercise.